(untitled) (Revista Chilena de Rehabilitación y Actividad Física, 2023)
In this letter, Carlos Gutierrez-Sanhueza expresses his gratitude to the editor for the publication of Ponce Navarrete’s (2023) article on the relationship between screen time and physical activity in adolescents. He emphasizes the relevance of the research in today’s society and the concerning data indicating a decrease in physical activity among young people. Additionally, he mentions other recent studies that demonstrate this inverse relationship and highlights the positive effects of physical activity on adolescents’ lives. In conclusion, Gutierrez-Sanhueza believes that the article is a valuable contribution to promoting healthy habits among young people.